Inversion of spin levels in exchange-coupled pairs under combined time reversal - Geru, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The method for transforming antiferromagnetic exchange interaction into the ferromagnetic one has been proposed for binuclear coordination compounds, which contain dimers consisting of iron or rare earth ions with arbitrary spins and having identical electronic configurations. The method is based on the time-reversal symmetry violation at isomorphic substitution of one of the dimer’s ions by a “time-reversed” ion, when the spin projection operators of only one of the dimer’s ions are reversed. Restoration of broken symmetry, accompanied by its transformation into combined time-reversal symmetry, is caused by the sign reversal of the exchange interaction constant J at isomorphic substitution. Experimental data confirm the proposed way of inverting the sign of J. The method for controlled synthesis of binuclear coordination compounds using specific isomorphic substitutions with “time-reversed” ions allows extending the class of coordination compounds characterized by ferromagnetic exchange interaction.